Abnormally slow reaction of oppositely charged ions: The kinetics of dopamine hydrochloride oxidation by ammonium peroxydisulfate. Issue 8 (21st April 2020) - Mezhuev, Yaroslav O.; Varankin, Alexander V.; Luss, Anna L.; Dyatlov, Valerie A.; Tsatsakis, Aristides M.; Stratidakis, Antonios K.; Korshak, Yuri V.
Abstract: The kinetic curves for oxidation of dopamine hydrochloride in aqueous solution in the presence of ammonium peroxydisulfate were obtained by UV–vis spectroscopy and potentiometry. It was shown that the reaction follows the first‐order kinetic equation and proceeds at a low rate. The values for the activation energy and the preexponential factor were determined as 75 kJ × mol −1 and 4 × 10 8  s −1, respectively. The activation entropy was found having a negative value of −89 J × mol −1  × K −1 . The first reaction order, the low preexponential factor and the negative activation entropy value for the reaction between the 2‐(3, 4‐dihydroxyphenyl)ethanammonium cation and the peroxydisulfate anion were explained by the formation of ionic associates, which slowly enter into the internal redox reaction.